OPTIMASI METODE ISOLASI DNA PADA Jatropha spp. - KRISTIANTO NUGROHO; RERENSTRADIKA T. TERRYANA; PUJI LESTARI (Jurnal Agroteknologi, 2015)
Physic nut is one of potential plant which produces biofuel. The presence of biofuel from physic nut is being expected could reduces the using of crude oil. It is important to do an intensive breeding program either convensionally or molecular based to improve new varieties of physic nut. DNA isolation is one of important step in molecular based activity. Physic nut has high latex content which makes isolation process become so difficult. The aim of this study is to find the technique of DNA isolation which can reduces the contaminants. There are two washing techniques that being used in this study, three times and five times washing. There are also two kinds of ascorbic acid which being used in this study, laboratory grade and 500 mg tablet vitamin C. The results showed that isolated DNA has a good of quality and quantity. The banding pattern of amplification clearly visible under UV light. The result showed that washing buffer three times is enough to produce good stock DNA. Besides, 500 mg tablet vitamin C can be used as a substitute for pure ascorbic acid in the process of DNA isolation when the pure ascorbic acid is not available in the laboratory.